A combination of endodontic therapy and root resection in furcation involvement case - Ernie Maduratna Setiawati (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Management of furcation involvement is one of major problems in clinical periodontology. The prognosis and treatment choices depend on the degree and severity of the lesion. Thus the decision for a specific treatment of furcation-involved tooth certainly depends on several factors. Tooth anatomy and the degree of furcation involvement are considered as the most important factors affecting the decision for one or more treatment plans mode. Purpose: The aim of this case report is to determine the management of class IV furcation involvement with the combination of endodontic therapy and root resection. Case: This study reported a case of 47 years old male patient who came to Periodontics clinic with tooth mobility, hypersensitivity and furcation involvement. Case management: One of the treatment is a combination of endodontic therapy and distal root resection. The results of these case could help the patient to have a better treatment for his furcation defect. Conclusion: Combining endodontic treatment and root resection were considered as an appropriate choice for retaining clinically-important trifurcation-involved tooth. Root resection had a better prognosis to treat periodontal problems than for non-periodontal problems. However, complex interdisciplinary treatment is important to be performed in the overall treatment plan.Latar belakang: Penatalaksanaan furkasi merupakan salah satu masalah di bidang periodontik. Rencana perawatan dan prognosis tergantung pada derajat keparahan furkasi. Untuk menentukan perawatan yang spesifik tergantung pada beberapa faktor. Anatomi gigi dan derajat keparahan furkasi merupakan faktor yang paling berpengaruh terhadap keputusan rencana perawatan. Tujuan: Tujuan laporan kasus ini adalah untuk menjelaskan penatalaksanaan furkasi kelas IV dengan perawatan kombinasi endodontik dan reseksi akar. Kasus: Penderita laki-laki usia 47 tahun datang ke klinik Periodonsia dengan keluhan gigi goyang, hipersensitif dan tampak adannya furkasi. Tatalaksana kasus: Dilakukan kombinasi perawatan endodontik dan reseksi akar distal. Hasil perawatan menunjukkan hasil yang lebih baik pada defek furkasi. Kesimpulan: Kombinasi perawatan endodontik periodontik dapat menjadi pilihan untuk mempertahankan gigi dengan furkasi. Reseksi akar dapat meningkatkan prognosis yang lebih baik. Perawatan interdisipliner yang kompleks dibutuhkan dalam membuat semua rencana perawatan.